2009
DOI: 10.1108/09578230910955809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of school design on student outcomes

Abstract: PurposeThe purpose of this study is to compare student achievement with three school design classifications: movement and circulation, day lighting, and views.Design/methodology/approachFrom a sample of 71 schools, measures of these three school designs, taken with a ten‐point Likert scale, are compared to students' outcomes defined by six parts of the Iowa Test of Basic Skills (ITBS): Reading comprehension, Reading vocabulary, Language arts, Mathematics, Social studies, and Science. Data are tested through re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
1
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 4 publications
(5 reference statements)
8
134
1
11
Order By: Relevance
“…To this end, design characteristics were grouped in terms of three sets of patterns such as movement and circulation, day lighting, and views (Tanner, 2009). And the interview was carried out and recorded.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…To this end, design characteristics were grouped in terms of three sets of patterns such as movement and circulation, day lighting, and views (Tanner, 2009). And the interview was carried out and recorded.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…The study of 3rd graders included measures for instructional neighborhoods and large group meeting places. Statistically significant relationships between the design measures and scores on the ITBS were found for all composite measures [47,48].…”
Section: Building Feature Categorymentioning
confidence: 88%
“…Research conducted by Tanner [47,48] and Barrett et al [43,45], using composite measures of different building features identified several interior design elements that have significant effects on student performance. Measures of design elements used in Tanner studies were from a larger instrument designed for assessing physical learning environments by researchers at the SDPL (University of Georgia's School Design and Planning Laboratory's).…”
Section: Building Feature Categorymentioning
confidence: 99%
See 1 more Smart Citation
“…School is the building that used for the teaching purposes, and classrooms are physical spaces that designed to support in person teaching and learning activities. There is a significant impact of the school building conditions on student achievement [4,5,6,7,8,9,10] because the built environment can influence users' behavior [11]. The relationship between schools building condition with student achievement was explained by Uline and Tschannen-Moran [9] who asserts that student from school with the better environment showed higher achievement.…”
Section: Literature Reviewmentioning
confidence: 99%